2021
DOI: 10.3389/fpsyg.2021.733405
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Online Surveys in Investigating Perceptions and Impressions of Faces

Abstract: Online experimental methods are used in psychological studies investigating the perceptions and impressions of facial photographs, even without substantial evidence supporting their reliability and validity. Although, the quality of visual stimuli is more difficult to control remotely, the methods might allow us to obtain a large amount of data. Then the statistical analysis of a larger volume of data may reduce errors and suggest significant difference in the stimuli. Therefore, we analyzed the reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…In contrast, the study by Kamatani et al [ 14 ] was conducted in a laboratory setting with screens of the same size. Even though some studies reported that online experiments are acceptable [ 39 – 41 ], it is possible that the inconsistencies in screen resolution underlie the failure to replicate the results of Kamatani et al [ 14 ]. Contrastingly, the mere exposure effect [ 38 ] was expected to increase perceived attractiveness in both HAF and LAF in Latter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the study by Kamatani et al [ 14 ] was conducted in a laboratory setting with screens of the same size. Even though some studies reported that online experiments are acceptable [ 39 – 41 ], it is possible that the inconsistencies in screen resolution underlie the failure to replicate the results of Kamatani et al [ 14 ]. Contrastingly, the mere exposure effect [ 38 ] was expected to increase perceived attractiveness in both HAF and LAF in Latter.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the issue of perceived familiarity with online experiments. Studies have shown that online experiments can be used to measure perceived attractiveness and trustworthiness from faces [39][40][41]. However, even with the existence of the beauty-is-good bias, it is not yet clear whether online experiments can accurately measure perceived familiarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were aware of the downside of an online experiment, such as less control over the display and viewing conditions, and the stimulus color, and the subsequent increase in variation of individual judgments. However, we were encouraged by a recent study by Hirao et al (2021) , who compared the perception of face obtained online and under controlled lab conditions. The authors conclude that results in the tasks performed online were broadly consistent with lab-based results, provided that a participant sample is sufficiently large to overcome a statistical error.…”
Section: Discussionmentioning
confidence: 99%
“…Similar demand also exists in basic psychology fields. Recently, we can collect participants' data online, which enables us to get a large sample size in spite of physical distancing, such as from COVID-19, while ensuring quality and reliable of data (Hirao et al, 2021). Thus, researchers may occasionally need to assess EFs as an additional variable.…”
Section: Introductionmentioning
confidence: 99%